A monograph on sleep and dream: their physiology and psychology - Cox, Edward W. (Edward William), 1809-1879 (Salt Lake City, UT : Project Gutenberg, 2021)
"A Monograph on Sleep and Dream: Their Physiology and Psychology" by Edward W. Cox is a scientific publication written in the late 19th century. The book delves into the complex phenomena of sleep and dreams, aiming to explain their physiological and psychological aspects through a thorough investigation of related facts and theories. The author highlights the importance of these concepts in understanding human consciousness and offers insights that can stimulate further research in psychology. The opening of the text introduces readers to various considerations surrounding the state of sleep, beginning with the fundamental necessity of sleep for human health. Cox elucidates that sleep is not simply a cessation of consciousness or vital action but a complex state where certain processes are actively functioning. He suggests that both physical and mental mechanisms remain engaged even as the body is resting. The discussion prompts readers to reflect on their own experiences with sleep and dreams, inviting them to ponder the mysteries of human cognition and the relationship between the body and the mind, setting the stage for a more detailed exploration in the subsequent chapters. (This is an automatically generated summary.)
Release date is 2021-02-22
Turgut Dincer and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Dreams; Sleep